AFFORDANCES OF STREET ENVIRONMENT FOR CHILD-FRIENDLY CITIES DURING HOME-SCHOOL JOURNEY IN OLD CITY ZONE OF MAKASSAR - Manikam, Arti; Said, Ismail (Plano Madani : Jurnal Perencanaan Wilayah dan Kota, 2016)
Home-school journey is part of children daily routine in many Indonesian cities and towns. Consequently, the street environment is an important component for children’s growth and development. In the last two decades, many urban centers have been identified as unsuitable for children’s home-school journey due to issues relating to high urban density and traffic congestion. Therefore, many children are denied the opportunity to experience the outdoor environment. Their life is centered at homes and within their schools. There are few studies that explore the affordances of street environment on home-school journey for less privileged children in old city zones. This study explores the affordances of street environment that influence children’s play behavior and performance during their home-school journey. The elements and environment of home-school journey play an important role in promoting children’s active free play toward their environment. This study observed 40 less-privileged children, aged 9 to 11, from low income families that walked to their schools in the old city zone of Makassar. Data on children’s activities and their perceptual responses on the street environment during the journey were elicited using one method which was children’s observation. The data were content analyzed using Nvivo software. The result revealed that the children displayed a variety of behaviors related to the social transaction, physical play and decision making. Affordances of street environment are associated with elements including buildings, vehicles and street furniture whereby the children’s direct engagements lead to indirect learning. Therefore, middle-childhood children recognized that the street environment is part of their routine living experience.